Synthesis method and application of MXene-based single-atom catalyst
By synchronously synthesizing single-atom catalysts in the synthesis of MXene in the MAX-phase ceramic material, the simple and efficient synthesis of MXene-based single-atom catalysts is achieved, and the problems of complex synthesis methods and unstable performance in the prior art are solved, and a catalyst with high purity and excellent performance is obtained.
Patent Information
- Application Number
- CN202510186903.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The existing MXene-based single-atom catalyst synthesis method is complex, the operation is cumbersome, the catalyst performance is unstable, and it is difficult to achieve in-situ construction of single-atom catalysts.
The single-atom catalyst is synchronized by synthesizing MXene in the MAX-phase ceramic material, and mixed with the metal single-atom precursor solution by LiF dissolved in HCl solution, and stirring and sonication under ice bath and water bath conditions to achieve a one-step synthesis of MXene-based single-atom catalyst.
The synthesis process is simplified, the purity and performance stability of the catalyst are improved, and the uniform dispersion and precise load of single atoms are achieved. It is suitable for a variety of metal single atom precursors, with strong versatility and wide application potential.
Smart Images

Figure CN119657188B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalysts, and in particular relates to a synthesis method and application of a MXene-based single-atom catalyst. Background Art
[0002] In today's fields of materials science and catalytic technology, MXene, as a new type of two-dimensional material, has shown great application potential in many fields due to its unique two-dimensional layered structure, excellent conductivity, zirconium specific surface area, good chemical stability and rich surface functional groups. It is regarded as one of the key materials to promote the advancement of energy storage and conversion technology.
[0003] At the same time, single-atom catalysts (SACs) have the advantages of theoretically 100% atomic utilization, unique and clear active site structure, and tunable electronic properties, which greatly improve the utilization efficiency of metal atoms, reduce the waste of resources such as precious metals, and reduce the cost of catalysts. The unique structure of single-atom catalysts enables them to exhibit excellent catalytic activity, selectivity, and stability in many catalytic reactions, providing new ideas and approaches for achieving efficient and green catalytic processes. They have application prospects that cannot be ignored in important fields such as chemical synthesis, environmental protection, and clean energy development. Therefore, the preparation of efficient and controllable single-atom catalysts has become an important topic in the field of catalysis research.
[0004] However, the current synthesis system of MXene-based single-atom catalysts generally faces multiple technical bottlenecks: its synthesis path mostly relies on multi-step heterogeneous integration strategies, involving the complex synergistic process of topological structure regulation of two-dimensional MXene substrates, surface functional group modification, and metal single atom anchoring. The traditional preparation paradigm is usually based on the concept of step-by-step synthesis - firstly, a few-layer MXene carrier is constructed by acid etching / intercalation stripping method, and then the metal single atom is loaded by post-treatment methods such as physical impregnation, wet chemical deposition or high-temperature pyrolysis. This discrete process has three core defects: (1) At the interface engineering level, the dynamic reconstruction of the MXene surface terminals (-O / -OH / -F) and the coordination competition with the metal precursors significantly weaken the anchoring efficiency of the active sites, resulting in uncontrollable aggregation of metal atoms and uneven density of active sites; (2) At the process control level, the suboptimal coupling of the solvent environment, thermodynamic conditions and kinetic processes in the multi-step operation easily leads to oxidation / stacking defects in the MXene structure, and the metal-carrier electronic interaction is difficult to precisely control; (3) At the technical and economic level, the oxygen-free operating environment required for the preparation of high-purity MXene, the low utilization rate of precious metal single atom precursors (usually <5%), and the lack of batch stability have jointly pushed up the material manufacturing cost. To achieve the large-scale preparation and promotion of MXene-based single-atom catalysts, it is urgent to develop new integrated synthesis strategies such as in situ self-assembly.
[0005] Therefore, there is an urgent need to develop a new, simple, efficient and widely applicable method for synthesizing MXene-based single-atom catalysts, which can realize the in-situ construction of single-atom catalysts in one step during the synthesis of MXene, effectively overcome the many defects of the existing technology, and thus lay a solid foundation for the industrial application of MXene-based single-atom catalysts in more fields. Summary of the invention
[0006] The present invention aims to solve the above-mentioned technical problems and provide a method for synthesizing a MXene-based single-atom catalyst. The method solves the problems existing in the prior art such as complex synthesis methods, cumbersome operations, unstable catalyst performance, etc., and realizes a simple and efficient synthesis of MXene-based single-atom catalysts. The prepared MXene-based single-atom catalysts have excellent performance.
[0007] The technical solution of the present invention is:
[0008] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0009] (1) Weighing LiF and dissolving it in HCl solution, and adding the metal single atom precursor solution under continuous stirring to obtain a mixed solution;
[0010] (2) Add MAX phase ceramic material to the mixed solution under ice bath conditions, transfer to a water bath, and continue stirring for 6-24 hours;
[0011] (3) washing by centrifugation with deionized water until the pH value of the solution reaches 6-7, dispersing the washed precipitate in deionized water at a solid-liquid ratio of 1:50-100 g / mL, and ultrasonically treating in an ice bath and inert atmosphere for 0.5-4 h;
[0012] (4) The solution after ultrasonic treatment is centrifuged and the upper layer of the solution is freeze-dried to obtain the MXene-based single-atom catalyst.
[0013] The method of the present invention solves the problems existing in the prior art, such as complex synthesis methods, cumbersome operations, and unstable catalyst performance. Through the method of the present invention, MXene-based single-atom catalysts with excellent catalytic performance can be efficiently and simply synthesized, and have potential in the application of electrocatalytic conversion. The method of the present invention innovatively realizes the simultaneous synthesis of single-atom catalysts in the process of synthesizing MXene from MAX phase ceramic materials. Different from the traditional step-by-step synthesis method, it greatly simplifies the synthesis process, reduces the synthesis steps and time cost, and effectively avoids the impurities that may be introduced during the step-by-step synthesis process and the problem that the single-atom dispersion and loading amount are difficult to accurately control due to multi-step operations. Importantly, the synthesis method of the present invention is universal and applicable to a variety of metal single-atom precursors. By selecting different metal precursors, different MXene-based metal single-atom catalysts can be synthesized, and can be flexibly adjusted according to different catalytic requirements, with strong versatility.
[0014] Preferably, in step (1) of the present invention, the concentration of the HCl solution is 6-14 mol / L, and the concentration of LiF is 0.06-0.12 g of LiF per milliliter of HCl solution, wherein too high or too low a concentration of LiF will affect the synthesis effect of MXene, and single-layer / few-layer MXene cannot be obtained.
[0015] Preferably, in step (1) of the present invention, the solute of the metal single atom precursor solution is one of manganese chloride monohydrate, ferric chloride hexahydrate, cobalt chloride dihydrate, nickel chloride hexahydrate, copper chloride dihydrate, zinc chloride, zirconium chloride, niobium pentachloride, and molybdenum chloride. Preferably, the solute concentration of the metal single atom precursor solution of the present invention is 1-5 mg / mL. If the concentration of the metal single atom precursor solution is too low, the metal single atom content will be too low, and the catalytic performance cannot be maximized; if the concentration of the metal single atom precursor solution is too high, the metal atoms will agglomerate to form metal nanoclusters or metal nanoparticles, which is not conducive to improving the catalytic performance of the catalyst. In order to obtain single-layer / few-layer MXene, preferably, in step (1) of the present invention, the volume ratio of the metal single atom precursor solution and the HCl solution is 1-20 μL: 2–200 mL.
[0016] Preferably, in step (2) of the present invention, the MAX phase ceramic material is Ti3AlC2. In order to obtain a single layer / few layers of MXene, the amount of the MAX phase ceramic material added in the present invention is preferably 0.06-0.12 g per milliliter of HCl solution in step (1).
[0017] Preferably, in step (2) of the present invention, the water bath environment temperature is controlled to be 25-70° C., and in step (3) of the present invention, the inert atmosphere is argon or nitrogen.
[0018] Application of MXene-based single-atom catalysts prepared by the synthesis method of the present invention in electrocatalytic conversion.
[0019] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0020] 1. The method of the present invention simplifies the synthesis process: the single-atom catalyst is synthesized simultaneously during the synthesis of MXene from MAX phase ceramic materials. Different from the traditional step-by-step synthesis method, it greatly simplifies the synthesis process and reduces the synthesis steps and time cost.
[0021] 2. The synthesis method of the present invention is universal: it is applicable to a variety of metal single-atom precursors. By selecting different metal precursors, different MXene-based metal single-atom catalysts can be synthesized, which makes the method flexible to adjust according to different catalytic needs and has strong versatility.
[0022] 3. The MXene-based metal single-atom catalyst synthesized by the method of the present invention has high purity: through one-step synthesis, the impurities that may be introduced in the step-by-step synthesis process and the problem that the single-atom dispersion and loading amount are difficult to accurately control due to multi-step operations are effectively avoided, thereby improving the purity of the MXene-based single-atom catalyst, which is conducive to its more stable and excellent performance in the catalytic reaction.
[0023] 4. The method of the present invention is precise and controllable: the dispersion and loading amount of single atoms can be precisely controlled. By optimizing the concentration of the metal single atom precursor solution, the addition amount and other parameters, the single atoms can be evenly dispersed and precisely loaded on MXene, so that each single atom can fully exert its catalytic activity and improve the utilization rate of the active sites of the catalyst.
[0024] 5. The MXene-based metal single-atom catalyst synthesized by the method of the present invention has broad application potential: Due to the excellent catalytic performance and stability of the MXene-based single-atom catalyst, it is widely used in energy conversion (such as fuel cells, water splitting to produce hydrogen, etc.), environmental remediation (such as pollutant degradation, carbon dioxide reduction, etc.) and organic synthesis and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a high-angle annular dark-field scanning transmission electron microscopy image of the Cu-SA / MXene single-atom catalyst prepared in Example 1 of the present invention.
[0026] Figure 2 This is a high-angle annular dark-field scanning transmission electron microscopy image of the Co-SA / MXene single-atom catalyst prepared in Example 2 of the present invention.
[0027] Figure 3 This is a high-angle annular dark-field scanning transmission electron microscopy image of the Ni-SA / MXene single-atom catalyst prepared in Example 3 of the present invention.
[0028] Figure 4 This is a high-angle annular dark-field scanning transmission electron microscopy image of the Cu-SA / MXene single-atom catalyst prepared in Example 4 of the present invention.
[0029] Figure 5 This is a high-angle annular dark-field scanning transmission electron microscopy image of the Cu-SA / MXene single-atom catalyst prepared in Example 5 of the present invention.
[0030] Figure 6 This is the linear sweep voltammetry curve of the electrocatalytic CO2 reduction reaction of the Cu-SA / MXene electrode prepared in Experimental Example 1 of the present invention.
[0031] Figure 7 This is the linear sweep voltammetry curve of the electrocatalytic N2 reduction reaction of the Co-SA / MXene electrode prepared in Experimental Example 2 of the present invention.
[0032] Figure 8 This is the Faradaic efficiency of the Co-SA / MXene electrode prepared in Experimental Example 2 of the present invention for the electrocatalytic N2 reduction reaction to synthesize NH3. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0036] (1) Preparation of metal single atom precursor solution: the concentration is 5 mg Cu / mL CuCl2·2H2O solution was used as the Cu single atom precursor solution;
[0037] (2) Weigh 1 g of LiF and dissolve it in 10 mL of HCl (9 mol / L) solution, and quickly add 20 μL of Cu single atom precursor solution under continuous stirring to obtain a mixed solution;
[0038] (3) In an ice bath, slowly add 1 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 35°C water bath and continue stirring at a constant speed for 24 h.
[0039] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH was ≥ 6, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:50 g / mL, and ultrasonically treated for 2 h in an ice bath and argon atmosphere;
[0040] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize MXene-based Cu single-atom catalyst (Cu-SA / MXene).
[0041] Figure 1 This is a spherical aberration electron microscopy image of the MXene-based Cu single-atom catalyst obtained in the above example. It can be seen from the figure that the metal Cu in the synthesized Cu-SA / MXene single-atom catalyst is atomically dispersed, and no Cu nanoclusters or Cu nanoparticles are observed. The content of Cu metal in the Cu-SA / MXene catalyst was determined to be 0.25 wt.% by inductively coupled plasma emission spectroscopy.
[0042] Example 2
[0043] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0044] Prepare metal single atom precursor solution: the concentration is 5 mg Co / mL CoCl2·2H2O solution was used as Co single atom precursor solution;
[0045] (2) Weigh 1 g of LiF and dissolve it in 10 mL of HCl (9 mol / L) solution, and quickly add 20 μL of Co single atom precursor solution under continuous stirring to obtain a mixed solution;
[0046] (3) In an ice bath, slowly add 1 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 35°C water bath and continue stirring at a constant speed for 24 h.
[0047] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH was ≥ 6, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:50 g / mL, and ultrasonically treated for 2 h in an ice bath and argon atmosphere;
[0048] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize the MXene-based Co single-atom catalyst (Co-SA / MXene).
[0049] Figure 2 This is a spherical aberration electron microscopy image of the MXene-based Co single-atom catalyst obtained in the above example. It can be seen from the figure that the metal Co in the synthesized Co-SA / MXene single-atom catalyst is dispersed at the atomic level, and no Co nanoclusters or Co nanoparticles are observed.
[0050] Example 3
[0051] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0052] (1) Preparation of metal single atom precursor solution: the concentration is 5 mg Ni / mL NiCl2·6H2O solution was used as Ni single atom precursor solution;
[0053] (2) Weigh 1 g of LiF and dissolve it in 10 mL of HCl (9 mol / L) solution, and quickly add 20 μL of Ni single atom precursor solution under continuous stirring to obtain a mixed solution;
[0054] (3) In an ice bath, slowly add 1 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 35°C water bath and continue stirring at a constant speed for 24 h.
[0055] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH was ≥ 6, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:50 g / mL, and ultrasonically treated for 2 h in an ice bath and argon atmosphere;
[0056] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize the MXene-based Ni single-atom catalyst (Ni-SA / MXene).
[0057] Figure 3 This is a spherical aberration electron microscopy image of the MXene-based Ni single-atom catalyst obtained in the above example. It can be seen from the figure that the metal Ni in the synthesized Ni-SA / MXene single-atom catalyst is dispersed at the atomic level, and no Ni nanoclusters or Ni nanoparticles are observed.
[0058] Example 4
[0059] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0060] (1) Preparation of metal single atom precursor solution: the concentration is 5 mg Cu / mL CuCl2·2H2O solution was used as the Cu single atom precursor solution;
[0061] (2) Weigh 1 g of LiF and dissolve it in 10 mL of HCl (9 mol / L) solution, and quickly add 40 μL of Cu single atom precursor solution under continuous stirring to obtain a mixed solution;
[0062] (3) In an ice bath, slowly add 1 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 35°C water bath and continue stirring at a constant speed for 24 h.
[0063] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH was ≥ 6, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:50 g / mL, and ultrasonically treated for 2 h under ice bath and nitrogen atmosphere;
[0064] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize MXene-based Cu single-atom catalyst (Cu-SA / MXene).
[0065] Figure 4This is a spherical aberration electron microscopy image of the MXene-based Cu single-atom catalyst obtained in the above example. It can be seen from the figure that the metal Cu in the synthesized Cu-SA / MXene single-atom catalyst is dispersed at the atomic level, and no Cu nanoclusters or Cu nanoparticles are observed. The content of Cu metal in the Cu-SA / MXene catalyst was determined by inductively coupled plasma emission spectroscopy to be 0.52 wt.%.
[0066] Example 5
[0067] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0068] (1) Preparation of metal single atom precursor solution: the concentration is 5 mg Cu / mL CuCl2·2H2O solution was used as the Cu single atom precursor solution;
[0069] (2) Weigh 1 g of LiF and dissolve it in 10 mL of HCl (9 mol / L) solution, and quickly add 40 μL of Cu single atom precursor solution under continuous stirring to obtain a mixed solution;
[0070] (3) In an ice bath, slowly add 1 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 35°C water bath and continue stirring at a constant speed for 24 h.
[0071] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH was ≥ 6, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:100 g / mL, and ultrasonically treated for 2 h in an ice bath and nitrogen atmosphere;
[0072] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize MXene-based Cu single-atom catalyst (Cu-SA / MXene).
[0073] Figure 5 This is a spherical aberration electron microscopy image of the MXene-based Cu single-atom catalyst obtained in the above example. It can be seen from the figure that the metal Cu in the synthesized Cu-SA / MXene single-atom catalyst is dispersed at the atomic level, and no Cu nanoclusters or Cu nanoparticles are observed. The content of Cu metal in the Cu-SA / MXene catalyst was determined by inductively coupled plasma emission spectroscopy to be 0.73 wt.%.
[0074] Example 6
[0075] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0076] Prepare metal single atom precursor solution: the concentration is 1 mg Sn / mL SnCl2 solution was used as Sn single atom precursor solution;
[0077] Weigh 12 g of LiF and dissolve it in 200 mL of HCl (14 mol / L) solution, and quickly add 10 μL of Sn single atom precursor solution under continuous stirring to obtain a mixed solution;
[0078] (3) In an ice bath, slowly add 24 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 25°C water bath and continue stirring at a constant speed for 6 h.
[0079] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH reached 7, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:50 g / mL, and ultrasonically treated for 0.5 h in an ice bath and nitrogen atmosphere;
[0080] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize MXene-based Sn single-atom catalyst (Sn-SA / MXene).
[0081] Example 7
[0082] A method for synthesizing a MXene-based single-atom catalyst comprises the following steps:
[0083] Prepare metal single atom precursor solution: the concentration is 3 mg Zr / mL ZrCl4 solution was used as Zr single atom precursor solution;
[0084] Weigh 0.12 g LiF and dissolve it in 2 mL HCl (6 mol / L) solution, and quickly add 1 μL of Zr single atom precursor solution under continuous stirring to obtain a mixed solution;
[0085] (3) In an ice bath, slowly add 0.16 g of Ti3AlC2 powder to the mixture. After the addition is complete, immediately transfer to a 70°C water bath and continue stirring at a constant speed for 6 h.
[0086] (4) After the reaction, the product was washed by centrifugation with deionized water several times until the pH reached 7, and then the washed precipitate was dispersed in deionized water at a solid-liquid ratio of 1:50 g / mL, and ultrasonically treated for 4 h in an ice bath and nitrogen atmosphere;
[0087] (5) The upper layer solution was collected by centrifugation (3500 rpm, 1 h) and freeze-dried to successfully synthesize the MXene-based Zr single-atom catalyst (Zr-SA / MXene).
[0088] According to the requirements, the solute of the metal single atom precursor solution can be replaced with one of manganese chloride monohydrate (MnCl2·H2O), ferric chloride hexahydrate (FeCl3·6H2O), niobium pentachloride (NbCl5), and molybdenum chloride (MoCl3). The remaining preparation steps and parameters can be the same as those in Example 1, and the corresponding MXene-based single atom catalyst can be prepared.
[0089] Experimental Example 1: Application of the Cu-SA / MXene catalyst prepared in Example 1 in electrocatalytic conversion
[0090] 6 mg of the Cu-SA / MXene catalyst prepared in Example 1 was weighed and added to a mixed solution of 0.5 mL of Nafion solution (0.05 t.%) and 0.5 mL of anhydrous ethanol, and then treated with ultrasound (300 W) for 1 h. The catalyst dispersion was sprayed on carbon paper and dried in a positive vacuum to obtain a Cu-SA / MXene electrode. The loading amount of the Cu-SA / MXene catalyst was determined to be approximately 1.0 mg / cm by the change in the weight of the carbon paper before and after spraying. 2 .
[0091] The Cu-SA / MXene electrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the Ag / AgC1 electrode was used as the reference electrode (located in the cathode chamber). The anode and cathode were separated by a proton exchange membrane, and the electrolyte was a 0.1 M KHCO3 solution. During the test, high-purity CO2 or Ar was continuously introduced into the electrolyte. The electrochemical linear sweep voltammetry test was used to evaluate the electrocatalytic CO2 reduction activity of the Cu-SA / MXene electrode. The linear scan rate was 10 mV / s and the voltage range was 0 V to -1.0 V vs RHE). Figure 6 As shown, after CO2 passed through the electrolyte, the Cu-SA / MXene electrode showed an enhanced reduction current density, confirming its excellent electrocatalytic CO2 reduction performance.
[0092] Experimental Example 2: Application of the Cu-SA / MXene catalyst prepared in Example 2 in electrocatalytic conversion
[0093] 6 mg of the Co-SA / MXene catalyst prepared in Example 2 was weighed and added to a mixed solution of 0.5 mL of Nafion solution (0.05 wt.%) and 0.5 mL of anhydrous ethanol, and then treated with ultrasound (300 W) for 1 h. The catalyst dispersion was sprayed on carbon paper and dried in a positive vacuum to obtain a Co-SA / MXene electrode. The loading amount of the Co-SA / MXene catalyst was determined to be approximately 1.0 mg / cm by the change in the weight of the carbon paper before and after spraying. 2 .
[0094] The Co-SA / MXene electrode was used as the working electrode, the platinum sheet was used as the counter electrode, and the Ag / AgC1 electrode was used as the reference electrode (located in the cathode chamber). The anode and cathode were separated by a proton exchange membrane, and the electrolyte was a 0.1 M KHCO3 solution. During the test, high-purity N2 or Ar was continuously introduced into the electrolyte. The electrochemical linear sweep voltammetry test was used to evaluate the electrocatalytic N2 reduction activity of the Co-SA / MXene electrode. The linear scan rate was 10 mV / s and the voltage range was 0 V to -1.0 V vs RHE). Figure 7 As shown in Figure 2, when N2 was passed through the electrolyte, the Co-SA / MXene electrode showed an enhanced reduction current density, confirming its excellent electrocatalytic N2 reduction performance. The results of the electrocatalytic N2 reduction synthesis of the Co-SA / MXene electrode are shown in Figure 2. Figure 8 As shown, it can be seen that the Co-SA / MXene electrode has excellent Faraday efficiency for electrocatalytic synthesis of ammonia. At a potential of -0.9 V vs RHE, the maximum Faraday efficiency for electrocatalytic N2 synthesis of ammonia is 63%.
[0095] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for synthesizing a MXene-based single-atom catalyst, characterized in that: The following steps are involved: (1) Weighing LiF and dissolving it in HCl solution, and adding the metal single atom precursor solution under continuous stirring to obtain a mixed solution; (2) Add MAX phase ceramic material to the mixed solution under ice bath conditions, transfer to a water bath, and continue stirring for 6-24 hours; (3) washing by centrifugation with deionized water until the pH value of the solution reaches 6-7, dispersing the washed precipitate in deionized water at a solid-liquid ratio of 1:50-100 g / mL, and ultrasonically treating in an ice bath and inert atmosphere for 0.5-4 h; (4) The solution after ultrasonic treatment is centrifuged and the upper layer of the solution is freeze-dried to obtain the MXene-based single-atom catalyst.
2. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (1), the solute of the metal single atom precursor solution is one of manganese chloride monohydrate, ferric chloride hexahydrate, cobalt chloride dihydrate, nickel chloride hexahydrate, copper chloride dihydrate, zinc chloride, zirconium chloride, niobium pentachloride, and molybdenum chloride.
3. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (1), the solute concentration in the metal single atom precursor solution is 1-5 mg / mL.
4. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (1), the concentration of the HCl solution is 6-14 mol / L, and the concentration of LiF is 0.06-0.12 g of LiF per milliliter of HCl solution.
5. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (1), the volume ratio of the metal single atom precursor solution and the HCl solution is: 1-20 μL: 2–200 mL.
6. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (2), the MAX phase ceramic material is Ti3AlC2.
7. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (2), the amount of MAX phase ceramic material added is 0.06-0.12 g per milliliter of HCl solution in the step (1).
8. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (2), the water bath environment temperature is controlled at 25-70°C.
9. The method for synthesizing a MXene-based single-atom catalyst according to claim 1, characterized in that: In the step (3), the inert atmosphere is argon or nitrogen.
10. Use of the MXene-based single-atom catalyst prepared by the synthesis method according to any one of claims 1 to 9 in electrocatalytic conversion.
Citation Information
Patent Citations
MXene-metallic composite and preparation method thereof
CN108091862A
Metal monatomic catalyst as well as preparation method and application thereof
CN112275303A